The Peshitta and Syro-Hexapla translations of Amos 1:3-2:16 - Verwijs, Petra. (Biblical Studies, Ancient Near East and Early Christianity E-Books Online, Collection 2016, ISBN: 9789004303812., 2016)
In The Peshitta and Syro-Hexapla Translations of Amos 1:3-2:16 , Petra Verwijs presents the result of a detailed study about the translation techniques used by two Syriac translations of the Biblical passage indicated. The Peshitta is the translation from a Hebrew original and the Syro-Hexapla from a Greek version. The book evaluates the unique characteristics of both through a detailed study of vocabulary and grammar. Previous scholarship has addressed issues of translation technique for the Peshitta of the Dodekapropheton, of which Amos 1:3-2:16 is a part. This is the first detailed study of any part of the Dodekapropheton of the Syro-Hexapla.